VD_FINDINFO HC / 2024 / 289 vom 29. Mai 2024 - VD Tribunal cantonal (2024)
REJET DE LA DEMANDE, BAIL À FERME AGRICOLE, MOTIVATION DE LA DEMANDE, RÉSILIATION, ABUS DE DROIT, PROLONGATION DU BAIL À FERME | 2 al. 2 CC, 16 LBFA, 27 LBFA, 9 LDFR, 311 al. 1 CPC (CH)